Study on the Flow Field of Hydrostatic Cavity of Impinging Freezer with Different Sizes by CFD - Gu Hanwen; Xie Jing; Wang Jinfeng (Zhileng xuebao)
Since traditional impact freezers have low freezing efficiency and high food weight loss, upper and lower impact freezers have gradually been recognized as new types with high efficiency by the food quick-freezing industry. In order to further optimize the freezing effect of the upper and lower impact freezers, a solid impact freezer with a hydrostatic cavity size of 4 m × 1.5 m × 2 m was taken as the baseline. The internal flow fields of five different dimensions of hydrostatic cavities including 4 m × 1.5 m ×1.5 m, 4 m × 2 m × 1.5 m, 4 m × 2 m × 2 m, 4 m × 2.5 m × 1.5 m, and 4 m × 2 m × 2 m were simulated by computational fluid dynamics (CFD) with the inlet pressure of 190 Pa and inlet flow rate of 4.4 m3/s. The internal heat transfer characteristics of the hydrostatic cavity were also analyzed comprehensively in terms of the nozzle outlet wind velocity of the impact freezer, vector distribution of the air flow on the surface of the steel belt, surface heat transfer intensity and heat transfer uniformity of the steel belt. The results showed that under the condition of the same inlet flow and constant pressure, only the outlet wind velocity of the cavity of dimensions 4 m × 1.5 m × 1.5 m differed slightly from that of the original size, and the wind velocities of the other sizes were slightly lower, but the range of change was not apparent. However, the heat transfer intensity and uniformity of this size were far less than those for the cavities with dimensions of 4 m × 2.5 m × 1.5 m and 4 m × 2.5 m × 2 m. In addition, although the heat transfer intensity of the hydrostatic cavity of dimensions 4 m × 2 m × 2 m was approximately 4.85% higher than that of the cavity of dimensions 4 m × 1.5 m × 2 m, its uniformity was poor and insufficient for it to be the optimal design. The heat transfer intensity of the cavities of dimensions 4 m × 2.5 m × 1.5 m and 4 m × 2.5 m × 2 m reached 177.76 and 177.39, which were approximately 6.81% and 6.59% higher than the surface heat transfer intensity of the steel belt under the original size. Additionally, the uniformity was the best. Combined with the above factors, the cavities of dimensions 4 m × 2.5 m × 1.5 m and 4 m × 2.5 m × 2 m were the optimal designs among the five sizes in terms of the outlet wind velocity, heat transfer intensity, and uniformity.